STUDY OF THE BOOK OF MUSNAD Al-SYAFI’I: Analysis of the Characteristics and Originality of Hadith which Rely on It - Qomarullah, Muhammad; Juriono, Juriono; Amin, Muhammad (RIWAYAH, 2024)
This paper aims to analyse the characteristics and originality of the traditions in the book Musnad Al-Shafi’i, a monumental work compiled by Imam Al-Shafi’i (d. 204 AH), which focuses on collecting the traditions of the Prophet Muhammad (peace be upon him) that serve as the basis for the formation of Islamic legal methodology, especially in the Shafi’i school of thought. Imam Al-Shafi’i is famous as a scholar of Fiqh not as a scholar of hadith, even though his teacher Imam Malik was a scholar of hadith, then Imam Ahmad ibn Hambal as his student was famous as a scholar of hadith. This study uses a descriptive-analytical approach by examining the quality and authenticity of the traditions contained in the Musnad, as well as analysing its contribution to the development of hadith science and Islamic fiqh. The Musnad of Al-Shafi’i contains a variety of traditions that have distinctive characteristics in terms of sanad and matan, and contains many traditions that are often the main reference in the process of interpreting the law. The method that the author uses with the data analysis of the book in the Musnad of Al-Shafi’i in which hadith scholars differ in opinion about the book originating from the imam Al-Shafi’i, approximately 500 traditions that are only from him, the rest are only much debated narrations from Al-Shafi’i through his students. As a result, there are many versions of the Musnad of Al-Shafi’i that need to be researched again, so it opens up the possibility for further research, both the history of the rijal al-hadis who quoted from Imam Al-Shafi’i. [Tulisan ini bertujuan untuk menganalisis karakteristik dan orisinalitas hadis dalam kitab Musnad Al-Syafi’i, sebuah karya monumental yang disusun oleh Imam Al-Syafi’i (w. 204 H), yang berfokus pada pengumpulan hadis-hadis Nabi Muhammad saw. yang dijadikan landasan dalam pembentukan metodologi hukum Islam, khususnya dalam mazhab Syafi’i. Imam Al-Syafi’i terkenal sebagai ulama Fiqh tidak sebagai ulama hadis, padahal guru beliau Imam Malik ialah ulama hadis, kemudian Imam Ahmad bin Hambal sebagai murid beliau terkenal sebagai ulama hadis. Penelitian ini menggunakan pendekatan deskriptif-analitis dengan menelaah kualitas dan keotentikan hadis-hadis yang terkandung dalam Musnad tersebut, serta menganalisis kontribusinya terhadap perkembangan ilmu hadis dan fiqh Islam. Kitab Musnad Al-Syafi’i mengandung berbagai hadis yang memiliki ciri khas dalam hal sanad dan matan, serta memuat banyak hadis yang sering kali menjadi rujukan utama dalam proses istinbath hukum. Metode yang penulis gunakan dengan analisis data Kitab pada Musnad Al-Syafi’i yang ulama hadis berbeda pendapat tentang kitab tersebut berasal dari imam Al-Syafi’i, lebih kurang 500 hadis yang hanya dari beliau, selebihnya hanya riwayat yang banyak diperdebatkan dari Al-Syafi’i lewat murid beliau. Adapun hasilnya Banyaknya versi dari Musnad Al-Syafi’i yang perlu diteliti lagi, sehingga membuka kemungkinan untuk penelitian yang lebih lanjut, baik riwayatnya dari rijal al-hadis yang menukil dari Imam Al-Syafi’i.]